Mafias y tráficos ilícitos: Tráfico ilícito de bebidas alcohólicas - Oliver, Francesc Xavier Moreno (Quadernos de criminología, 2022)
The manufacture, smuggling and sale of illicit alcoholic beverages represents tax fraud and a significant risk to the health of consumers. The mafias and criminal gangs (BACRIM) specialized in this lucrative illegal trade distribute the aforementioned drinks on the black market. Unscrupulous sectors of the hotel industry are the main buyers of these prohibited drinks. It is a criminal market that in recent years has been increasing its activity.